Analysis The Impact Of Religiosity On The Intention To Pirate Digital Products In Indonesia - Dade Irwan Sunardi; Arif Hartono (UNIVED Press, 2024)
This study aims to test and analyze the impact of religiosity on the intention to commit digital product piracy by integrating religiosity, ethics, and the theory of planned behavior theories. The objects were websites and platforms (such as Bolasiar.com, IndXXI, Spotify, Netflix, Video, Telegram, and the like). This study uses primary data collected through an online survey of 200 respondents. This research uses a purposive sampling technique. The hypotheses proposed were tested using Structural Equation Modelling (SEM). This study shows that variables such as attitude, subjective norms, perceived benefit, and intrinsic religiosity have positively influence on intention to pirate digital products. By contrast, moral obligation has a negative impact.